Constructing sleep health: understanding risks and interventions in the New Zealand roofing industry - Polaczuk, Chris; Dale, Kelly; Matt (New Zealand Journal of Health and Safety Practice, 2024)
The study investigated sleep health in terms of obstructive sleep apnoea and chronic insomnia amongst the Roofing trade in the New Zealand construction industry. Despite efforts to support workers, intervention uptake remained low, indicating a necessity for more tailored approaches. Addressing work-related stressors and offering sleep health education could enhance treatment acceptance. Future research should investigate cultural and experiential influences on sleep quality. However, limitations like the small sample size and convenience sampling must be acknowledged. In conclusion, while the study provides valuable insights, further exploration and nuanced interventions are imperative to address sleep-related challenges in the construction industry effectively.